Knowledge and awareness on Balo's disease among dental students: A survey - Bathala Ananya; Vishnupriya Veeraraghavan; S Kavitha; J Selvaraj; R Gayathri (Wolters Kluwer Medknow Publications, 2022)
Balo's disease is an uncommon central nervous system disorder causing demyelination and is a form of multiple sclerosis. Concentric sclerosis, leukoencephalitis periaxialis concentrica, is also known as Balo's disease. Concentric sclerosis signalizes the bands of intact myelin and alternating rings of myelin loss present in several parts of the brainstem and brain. The present study aimed to assess and create awareness about Balo's disease among dental undergraduates. The study included an online survey about the knowledge and awareness of Balo's disease among dental students. A questionnaire was prepared, uploaded, and distributed in an online portal. The latest software version of SPSS was used to analyze the collected data. Descriptive statistical analysis and Chi-square test were done, and the P value was calculated. The survey showed that 54.55% of males and 45.45% of females participated in this survey. Most of the respondents (87.88%) knew about Balo's disease, whereas only 12.12% of participants were not aware of the disease. It was found that most of dental students are aware of Balo's disease. The study also showed that male respondents are more aware than the females.